Resting tongue posture in infants – norm and function disorders - Borowiec, Agnieszka; Lorenc, Anita (Papers in Linguistics, 2025)
The aim of this article is to describe the normal resting posture of the tongue in infants and its disorders, presented against the backdrop of the anatomical and functional development of the orofacial region during the prenatal period. The study includes description of the anatomical structure of the tongue and the functional stabilization of the resting posture of the stomatognathic system as presented in the selected literature on the subject. It also features analyses of original research on the normal and dysfunctional resting posture of the tongue in ten infants (5 typically developing and 5 with primary function disorders), conducted as part of a multiple case study. The results demonstrate that there is an automatic, effortless control mechanism of the orofacial region present from birth, in which the resting posture of the tongue plays a key and overriding role in relation to other primary functions. The posture’s pattern will have a direct effect on the development of articulation, and the research presented in this study is therefore of fundamental importance in terms of the linguistic foundations of speech therapy.